Role of inter-hemispheric transfer in generating visual evoked potentials in V1-damaged brain hemispheres. (February 2015) - Kavcic, Voyko; Triplett, Regina L.; Das, Anasuya; Martin, Tim; Huxlin, Krystel R.
Abstract: Partial cortical blindness is a visual deficit caused by unilateral damage to the primary visual cortex, a condition previously considered beyond hopes of rehabilitation. However, recent data demonstrate that patients may recover both simple and global motion discrimination following intensive training in their blind field. The present experiments characterized motion-induced neural activity of cortically blind (CB) subjects prior to the onset of visual rehabilitation. This was done to provide information about visual processing capabilities available to mediate training-induced visual improvements. Visual Evoked Potentials (VEPs) were recorded from two experimental groups consisting of 9 CB subjects and 9 age-matched, visually-intact controls. VEPs were collected following lateralized stimulus presentation to each of the 4 visual field quadrants. VEP waveforms were examined for both stimulus-onset (SO) and motion-onset (MO) related components in postero-lateral electrodes. While stimulus presentation to intact regions of the visual field elicited normal SO-P1, SO-N1, SO-P2 and MO-N2 amplitudes and latencies in contralateral brain regions of CB subjects, these components were not observed contralateral to stimulus presentation in blind quadrants of the visual field. In damaged brain hemispheres, SO-VEPs were only recorded following stimulus presentation to intact visual field quadrants, via inter-hemispheric transfer. MO-VEPs were only recorded from damaged left brain hemispheres, possibly reflecting a native left/right asymmetry in inter-hemispheric connections. The present findings suggest that damaged brain hemispheres contain areas capable of responding to visual stimulation. However, in the absence of training or rehabilitation, these areas only generate detectable VEPs in response to stimulation of the intact hemifield of vision. Highlights: Motion-onset VEPs reflect global motion perception in cortically blind subjects. In damaged brain hemispheres, VEPs are only elicited via inter-hemispheric transfer. Intact hemispheres drive activity of spared visual areas in V1-damaged hemispheres.